Development of a two-layer 3D equine endometrial tissue model using genipin-crosslinked collagen scaffolds and 3D printing - Sawita Santiviparat; Setthibhak Suthithanakom; Sudchaya Bhanpattanakul; Sayamon Srisuwattanasagul; Kai Melde; Tom A. E. Stout; Theerawat Tharasanit (Scientific Reports)
Abstract Advances in endometrial tissue engineering have enabled the combination of modified scaffolding materials with modern cell culture technologies. Genipin and three-dimensional (3D) printing have advanced cell-tissue engineering by enabling the precise layering of cell-containing matrices while ensuring low cytotoxicity. This study aimed to advance equine endometrial tissue engineering by designing customized collagen scaffolds using 3D printing technology, while optimizing the genipin concentration to avoid toxicity. Genipin was tested at concentrations of 4, 2, 1, 0.5, 0.25, 0.125, and 0 mM on equine endometrial epithelial cells (eECs) and mesenchymal stromal cells (eMSCs). Its effects on cell morphology and scaffold properties were evaluated in collagen-based conventional equine endometrial tissue (3D-ET) by assessing percentage of cells spreading within each genipin concentration. Additionally, genipin-collagen scaffolds at 2, 1, 0.5, 0.25, and 0 mM were analyzed for viscoelastic properties using rheological testing. Based on these assessments, 0.5 mM genipin was identified as the optimal concentration and was to develop in vitro 3D-ET. Key 3D printing parameters, including extrusion pressure, printing temperature, pre-printing time, and velocity, were optimized. The structural integrity of the advanced 3D-ET was assessed via phase contrast microscopy. Cellular characterization was performed using Pan-cytokeratin and Vimentin staining. For the characterization of printed 3D-ET, mucin production was assessed using Alcian blue staining, while estrogen receptor alpha (ERα) expression was evaluated by immunofluorescence. A study of oxytocin-stimulated prostaglandin synthesis capacity was performed in an advanced 3D-ET for 24 h, and expression of key genes was analyzed quantitatively using real-time PCR. Genipin exhibited dose-dependent toxicity, with 0.5 mM identified as the optimal concentration based on its support of proliferative activity, cell morphology, and viscoelastic properties. Only eMSCs were successfully 3D-printed in a collagen scaffold with 0.5 mM genipin. While the 3D-printed biomaterial failed to support eECs viability; eECs survived and formed glands only when a conventional seeding method was used. Consequently, a dual-layer 3D-ET model was developed in which eMSCs were printed with 0.5 mM genipin-collagen, and eECs were overlain using conventional methods. This model preserved the structural integrity necessary for glandular-like development and maintained the functional characteristics of equine endometrial tissue. Mucin production was observed, while ERα was detected in the cytoplasm and translocated into the nucleus.Notably, after OT challenge prostaglandin-endoperoxide synthase 2 (PTGS2) expression was significantly elevated in the treatment group compared to controls (p < 0.05). This advanced 3D-ET model offers a robust platform for studying tissue-specific functions and could be further developed by incorporating immune or endothelial cells or creating complex structures such as glands or vessels.